Role of gut microbiota: Obesity and NAFLD - Gangarapu, Venkatanarayana; Yıldız, Kemal; İnce, Ali Tüzün; Baysal, Birol (Turkish Journal of Gastroenterology, 2014)
Abstract Non-alcoholic fatty liver disease (NAFLD) is a leading cause of chronic liver disease in developed countries. Obesity is the most important risk factor for metabolic syndrome and NAFLD. Accumulated evidence has revealed that gut microbial compositional changes may be associated with more energy harvesting from the diet, which promotes increased fatty acid uptake from adipose tissue and shifts lipid metabolism from oxidation to de novo production. Furthermore, changes in intestinal barrier function contribute to metabolic endotoxemia in the form of low-grade microbial inflammation. Persistent inflammation exacerbates NAFLD progression. In this review, we discuss the role of gut microbiota in obesity and NAFLD.